Community Agreeableness and Inter Organizational Knowledge Sharing In Improving Business Sustainability - Dita Prameswari; Winarsih (JMBPreneur: Jurnal Manajemen, Bisnis, dan Kewirausahaan, 2021)
Background: In the era of knowledge-based economy and business model 4.0, the involvement of a company in a business community is important to improve business sustainability. The business community is a group consisting of a number of people who have the same business values in each individual. They can interpret these values into business groups where they can interact with each other for the progress of their business and especially for sustainable business. Purpose: The purpose of this research is to develop two main concepts that are believed to support the sustainability of a business. The two concepts are Community Agreeableness and Inter Organizational Knowledge Sharing. This concept is derived from one of the big five personalities 'agreeableness' and 'knowledge sharing' which is applied in a business community. Methods: The research method used is a literature survey to define concepts and develop measurements. Results: The results of the study have found a construct in an effort to increase business sustainability, namely the new concept of community agreeableness and inter organizational knowledge sharing Conclusion: Community agreeableness will make it easier for an organization to be willing to share knowledge and vice versa regarding its business activities to community members. Thus, in the long term, it is expected to increase business sustainability